2003
DOI: 10.1097/00005344-200310000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilative Effects of Urocortin II via Protein Kinase A and a Mitogen-activated Protein Kinase in Rat Thoracic Aorta

Abstract: Four corticotropin-releasing factor (CRF)-related peptides have been found in mammals and are known as CRF, urocortin, urocortin II, and urocortin III (also known as stresscopin). The three urocortins have considerably higher affinities for CRF receptor type 2 (CRF R2) than CRF, and urocortin II and urocortin III are highly selective for CRF R2. In the present study, the authors examined the hypothesis that urocortin II or urocortin III, in addition to urocortin, produces vasodilation as a candidate for natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…Indeed, intravenous administration of Ucn1 in experimental HF induces sustained reductions in cardiac preload and afterload, increases in cardiac output (CO), marked decreases in a range of circulating vasoconstrictor/volume-retaining factors, and augmentation of renal function. 10 Preliminary reports on the more recently discovered Ucn2 indicates that this peptide, like Ucn1, also exhibits strong expression in cardiac and vascular tissues 2 and has vasodilator 6,11 and cardiac contractile actions in normal rodents. 12 A single report of Ucn2 administration in a murine model of HF demonstrates that the peptide produces inotropic and lusitropic effects and improves CO in this disease.…”
Section: Editorial P 3544 Clinical Perspective P 3632mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, intravenous administration of Ucn1 in experimental HF induces sustained reductions in cardiac preload and afterload, increases in cardiac output (CO), marked decreases in a range of circulating vasoconstrictor/volume-retaining factors, and augmentation of renal function. 10 Preliminary reports on the more recently discovered Ucn2 indicates that this peptide, like Ucn1, also exhibits strong expression in cardiac and vascular tissues 2 and has vasodilator 6,11 and cardiac contractile actions in normal rodents. 12 A single report of Ucn2 administration in a murine model of HF demonstrates that the peptide produces inotropic and lusitropic effects and improves CO in this disease.…”
Section: Editorial P 3544 Clinical Perspective P 3632mentioning
confidence: 99%
“…Although several studies have detailed the cardiovascular actions of Ucn2, 6,11,12 there are no data available on the effects of Ucn2 on other vasoactive peptide systems or on renal parameters in either normal or heart-diseased conditions. This information is crucial given the impact of hormonal activation and renal function on the evolution of overt HF and cannot be predicted from the data available on Ucn1 because the mechanisms (and receptor subtypes) contributing to these responses are unknown.…”
Section: Editorial P 3544 Clinical Perspective P 3632mentioning
confidence: 99%
“…10,12 Marked inotropic and lusitropic effects, as well as a reduction of peripheral resistance, have been reported for Ucn2 in a recent study in wild-type mice and cardiomyopathic mice with congestive heart failure (CHF) 18 and, together with beneficial renal and endocrine effects, in pacinginduced CHF in sheep. 19 Potent vasodilatory effects by Ucn2 were reported in rat thoracic aorta 20 and in human arteries. 21 Intravenous application of Ucn2 induced a dose-dependent rapid and highly significant BP reduction in normotensive rats.…”
mentioning
confidence: 98%
“…It has also been demonstrated that urocortin 2 protected neonatal cardiac myocytes in vitro when administered before hypoxia/ischemia (Ikeda et al, 2005), which suggests that calcium channels may play some roles since ischemia and hypoxia damage is highly associated with Ca 2 + -overload. Furthermore, it was reported that urocortin 2 played the cardiovascular protective role via protein kinase A (PKA) and mitogen-activated protein kinase (MAPK) pathway, which might lead to changes in the intracellular Ca 2 + (Kageyama et al, 2003). Intracellular calcium plays a key role in gene expression, neuronal migration, neurotransmitter release (Catterall, 1998), and is involved in the developing of some neuronal degenerative diseases such as Alzheimer's and Parkinson's diseases, which are highly associated with calcium overload (Verkhratsky and Toescu, 2003).…”
Section: Introductionmentioning
confidence: 99%